2014
DOI: 10.4236/ajps.2014.57114
|View full text |Cite
|
Sign up to set email alerts
|

Sward Structural Characteristics and Performance of Beef Heifers Reared under Rotational Grazing Management on Campos Grassland

Abstract: This study aimed to evaluate the effect of two rest intervals on structural sward characteristics and productive performance of beef heifers reared on Campos grassland managed on rotational grazing. The treatments were two intervals between grazing of 375 and 750 DD (degree days), based on thermal cumulative sum for leaf expansion of native grasses belonging to two functional groups. The experimental design was a randomized complete block design with two treatments and three replications. The tested animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The blocking criterion was the relief. Details regarding management can be found in Barbieri et al ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blocking criterion was the relief. Details regarding management can be found in Barbieri et al ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, ruminants commonly have grazing times between 450 and 600 min/day in temperate pastures and rarely forage <360 min/day, with times that may exceed 760 min/day on subtropical and tropical pastures ( 4 , 5 ). In the southern Brazil Campos grasslands ( 6 ), without limitations to inhibit potential intake (e.g., sward height or herbage mass), the time spent grazing commonly ranges between 500 and 650 min/day ( 7 9 ), regardless of the grazing method used ( 10 ). This variation in grazing time indicates potentially diverse situations and challenges that animals can face, even in situations with abundant forage allowance, attesting to the complex interaction of animals with plants and sward structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research results have shown that the potential productivity of this management goes far beyond of what is usually recorded at commercial farms, making possible to obtain animal performance necessary to achieve 65 to 70% of adult weight, a goal for mating at 24 months of age (QUADROS et al, 2011;BARBIERI et al, 2014). Nevertheless, the influence of this management proposal (rotational grazing with rest intervals according to morphogenetic traits) on animal's behavior is not already explored.…”
Section: Introductionmentioning
confidence: 99%
“…() reported an average daily gain of approximately 0·28 and 0·18 kg for heifers reared on this natural grassland managed with grazing interval of 375 and 750 DD respectively. In the same area and with the same grazing protocol, heifers with similar BW, and with 0·36 kg per day liveweight gain, have an estimated dry‐matter intake of 2·04% of their BW (Barbieri et al ., ). Thus, it follows that these heifers, with an average DM intake of leaf blade equivalent to 1·40% of their BW, obtained nearly 68% of their daily DM intake consisting of leaves from the five studied grasses.…”
Section: Discussionmentioning
confidence: 97%